Member Satisfaction in Cooperative Financial Services: The Roles of Internal System Quality, Service Quality, and Trust - Agen Driyanto; Fahrudin Fahrudin (Growth: Journal Management and Business, 2026)
This study aims to analyze the influence of the quality of the member data management application system, service quality, and member trust on the level of member satisfaction at the Amanah Tongas Credit Union Savings and Loan Cooperative. The study uses a quantitative approach with a causal associative research type. The study population was 2,251 active members, while the sample was 340 respondents determined using the Slovin formula with a simple random sampling technique. Data collection was carried out through distributing questionnaires, observation, and documentation. Data analysis used IBM SPSS Statistics version 26 which included validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, partial tests (t-tests), simultaneous tests (F-tests), and coefficients of determination (R²). The results showed that the quality of the member data management application system had a positive but not significant effect on the level of member satisfaction. Conversely, the quality of service quality and member trust had a positive and significant effect on the level of member satisfaction. Simultaneously, the quality of the member data management application system, service quality, and member trust had a significant effect on the level of member satisfaction. Research findings show that improving service quality and strengthening member trust are the main factors in increasing member satisfaction, while developing application systems is still needed to support the effectiveness of cooperative administration and services.